Systematic profiling of chemotherapeutic drug response to EGFR gatekeeper mutation in non-small cell lung cancer. (October 2016) - Yao, Jun; Zhao, Xiaojuan; Ding, Xi
Graphical abstract: Highlights: A systematic profile of chemotherapeutic drug response to kinase gatekeeper mutation is created. The first-line therapy is found to cause acquired resistance upon the mutation. Staurosporine analog K252a is a good candidate for selectively targeting mutant over wild-type kinase. The mutation defines a number of additional noncovalent interactions at kinase–K252a interface. Abstract: The epidermal growth factor receptor (EGFR) targeted therapy has been established as a routine strategy for treating non-small cell lung cancer (NSCLC). However, the gatekeeper mutation T790M in EGFR active site can confer generic resistance to tyrosine kinase inhibitors (TKIs), largely limiting the clinical applications of chemotherapeutic drugs in NSCLC. Here, a combined method of computational analysis and growth inhibition assay was described to systematically investigate the molecular response profile of wild-type–sparing and mutant-resistant inhibitors to the EGFR T790M mutation. The profile is highly consistent with previous clinical observations; three first-line chemotherapeutic drugs Gefitinib, Erlotinib and Lapatinib are established with acquired resistance upon the mutation. In addition, it was found that the alkaloid compound K252a, a Staurosporine analog isolated from Nocardiopisis sp., can selectively target the EGFR T790M mutant over wild-type kinase (23-fold selectivity), suggesting that the compound is good lead candidate for development of T790M mutant-selective inhibitors. Structural analysis revealed that the mutation-resulting Met790 residue does not induce steric hindrance to the EGFR T790M–K252a complex system, while a number of hydrophobic forces, van der Waals contacts and S⋯π interactions are observed between the aromatic rings of K252a and the sulfhydryl group of Met790, contributing considerable stabilization energy to the system.